Marginal zone B cells exacerbate endotoxic shock via interleukin-6 secretion induced by Fcα/μR-coupled TLR4 signalling - Shin-ichiro Honda (Nature Portfolio, 2016)
Marginal zone B cells are mostly characterized in the context of host defense against bacterial blood-borne pathogens. Here the authors show that TLR4 signaling in these cells requires Fcα/μR (CD351) and that they are a major source of IL-6 in a mouse model of sepsis.